PERANCANGAN DESAIN SISTEM TANDA JALAN & TEMPAT WISATA (STUDI KASUS : YOGYAKARTA DAN SEKITARNYA) - Septarina, Sri Wahyuning (LPPM STMIK STIKOM Indonesia, 2018)
Increased income of Indonesia in the form of foreign exchange one of them is because of tourism. The second tourism destination in Indonesia after Bali that attracts the attention of foreign tourists and local tourists is Yogyakarta. The attraction of this city is the legacy of nature and cultural tourism that continues to be maintained values ââand traditions, because it is the largest capital of the development of tourism in the city. Along with the city of Yogyakarta is being clean up to realize itself as a tourist destination in Indonesia, it is worth noting some very basic things one of which is a system of tourism signs that exist today. Not apart from the nickname of the city of Jogjakarta as a cultural center, it is inevitable that cultural knowledge increasingly faded and forgotten. Therefore it must be preserved from simple-looking things but provide informative travel information. the tourism sign system which is part of the traffic sign system sub-section needs to be improved. The tourism sign system is one form of information that is short and clear which involves many disciplines. With the approach of various disciplines are expected to apply and its use can be maximally and do not forget the elements of local culture. The results of the test show good response from some related parties as suggestions and enter for infrastructure improvement in Yogyakarta.